2013
DOI: 10.1007/s00268-013-2257-5
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Whipple: Do or Don’t After Severe Pancreaticoduodenal Injuries? An Analysis of the National Trauma Data Bank (NTDB)

Abstract: Compared to non-PDT, PDT did not result in improved outcomes despite a lower physiologic burden among PDT patients. More conservative procedures for high-grade injuries of the pancreaticoduodenal complex may be appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 34 publications
2
47
2
3
Order By: Relevance
“…Indeed, most pancreaticoduodenal injuries are low grade and can be managed non-operatively; even so when a surgical approach has been agreed, more patients can be treated by lavage-drainage and then with total parenteral nutrition in ICU, eventually reserving an EPD as a two-stage procedure [9,13,14]. The largest study on EPD for trauma to date consists of only 18 patients from a single center [9], and a recent study comparing EPD with non-EPD for severe pancreaticoduodenal injuries, concludes that more conservative procedures for high grade injuries, like primary repair, drainage, duodenal exclusion, partial pancreatectomy, may be appropriate [15]. The first description of the use of EPD in two trauma patients dates back to 1964 by Thal [16], and its reported incidence for pancreatic injuries ranges from 0.075% to 5% [17e19].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, most pancreaticoduodenal injuries are low grade and can be managed non-operatively; even so when a surgical approach has been agreed, more patients can be treated by lavage-drainage and then with total parenteral nutrition in ICU, eventually reserving an EPD as a two-stage procedure [9,13,14]. The largest study on EPD for trauma to date consists of only 18 patients from a single center [9], and a recent study comparing EPD with non-EPD for severe pancreaticoduodenal injuries, concludes that more conservative procedures for high grade injuries, like primary repair, drainage, duodenal exclusion, partial pancreatectomy, may be appropriate [15]. The first description of the use of EPD in two trauma patients dates back to 1964 by Thal [16], and its reported incidence for pancreatic injuries ranges from 0.075% to 5% [17e19].…”
Section: Discussionmentioning
confidence: 95%
“…However, when massive nonreconstructable injuries involving pancreas, duodenum, common bile duct, or destruction of the ampulla of Vater are evident, the indication to EPD is unavoidable. In these situations though the majority of EPD are performed within 6 h of admission [15]. This data is surprising because these trauma patients should be managed with modern damage control principles (arrest hemorrhage, temporary control contamination, restore physiologic balance) deferring surgery to more favorable conditions; on the other hand, it is demonstrated that patients who underwent EPD for complex trauma died much later than patients with a non-EPD, who died with a median of only one day, usually due to hemorrhage [15].…”
Section: Discussionmentioning
confidence: 99%
“…In the small cohort of patients who have maximal injuries of the pancreatoduodenal complex and in whom there is no other rational surgical option for survival, a salvage pancreatoduodenectomy may be necessary [1,[12][13][14]. However, surgical intervention of such magnitude in those who are severely injured can only be contemplated in haemodynamically stable patients.…”
Section: Introductionmentioning
confidence: 99%
“…1,6,7 Recent data from the National Trauma Data Bank show that far from being a procedure of last resort, approximately 20% of trauma PDs occurred in patients who did not have severe (Grade IV or V) injuries to either the pancreas or duodenum. 8 Although patients surgically managed with an operation other than PD had significantly lower systolic blood pressures and Glasgow Coma Scale (GCS) scores, there was no significant difference between morbidity and mortality in the PD-versus nonYPD-treated groups. 8 These findings suggest two possible faults in reflexive treatment of combined pancreaticoduodenal trauma with PD.…”
mentioning
confidence: 97%
“…8 Although patients surgically managed with an operation other than PD had significantly lower systolic blood pressures and Glasgow Coma Scale (GCS) scores, there was no significant difference between morbidity and mortality in the PD-versus nonYPD-treated groups. 8 These findings suggest two possible faults in reflexive treatment of combined pancreaticoduodenal trauma with PD. First, PD is performed in a significant minority of cases where it is not warranted.…”
mentioning
confidence: 97%